Knowledge and accessibility of Muslim women to the law on post-divorce financial support. - Hasbullah @ Abdullah, Muslihah; Mohd Zin, Najibah; Wok, Saodah (IIUM Press, 2010)
The main objective of the study was to determine the Muslim women's knowledge and accesibility to the law on post divorce financial support particularly that which relates to 'iddah maintenance, mut'ah,arrears of maintenance and child maintenance. The data was collected using self administered questionaire. The sample was 201 divorced women recruited from the recorded cases for the period 2003-2005 inthe Subordinate Shariah Courts of Hulu Langat and Gombak Timur, Sekangor. The findings indicate that almost all respondents (99%) have high level of knowledge on the legal rights to post divorce financial support. However, more than two-third of the respondents (70%) had low level of accessibility to the law when claiming for post divorce financial support. The study suggests that although divorced women might have better access to legal information through reading and socialisation, the problem regarding the attitude of the court's officer, and lawyers. the complexity of the court procedures, the uncooperative attitudes and the non-compliance of the ex-husbands to the court ordered financial support did impede their accessibility to the law.